SINGLES ON THE CONSUMER MARKET IN POLAND - Słaby, Teresa (Acta Scientiarum Polonorum. Oeconomia, 2019)
The socio-economic changes taking place in Poland in the twenty-first century caused, among others, the changes of the family model, which resulted in a strong increase in the number of one-person households (the so-called singles). It is estimated that the share of modern singles at different ages will increase by 2030 in a global perspective by about 20%, especially in big cities. In Poland in 2017, the fraction of these households was 23.5%. Satisfying the various needs of singles should shape the market of goods and services addressed to this group of consumers. The author, using the data from the GUS (Central Statistical Office) household budget surveys in 2015 and the results of a co-authored own survey carried out in 2017, investigated consumer behaviours of singles from large cities in two age groups of young people and opinions about the degree of preparation of the Polish market, including the Internet, to meet their needs. Diagnostic and application usefulness is expressed by information important for the marketing activity of enterprises that will adjust their market offer to the expectations of a growing group of Polish one-person households.